PERBAIKAN BEBAN KERJA PEGAWAI TIDAK TETAP BADAN PERTANAHAN NASIONAL MELALUI REDESIGN SYSTEM - Andriani, Meri; Hasan, Muhammad Thaib; Fradila, Sondy (TALENTA Publisher, 2017)
National Defence Agency is a Non-Ministerial Government Institution is which under and responsible to President and headed by a Chief. Land Agency produces products that prioritize on quality and legacy of law. Human resources have a major role in every company's activities. Although supported by facilities and infrastructure and excessive resources, but without the support of reliable resources, activities in an agency / company will not be resolved properly. Workload is a situation where workers are faced with tasks that must be completed at a certain time. The Problems in this research is the amount of workload for the employees both mentally and physically is too much that making mistakes and fatigue in working. The study aims to redesign the system in overcoming the workload experienced by the giving survey to the workers at the Land Agency at Langsa City.The method used is workload objectively by measuring the mental workload through the pulse, the questionnaire to know the amount of workload that affects work stress. The result of the research showed that the increase of pulse before working to the pulse after work, the average increase of the pulse of 47,9 beats / minute. Kasdiovasculer expense (% CVL) employees claimed to require repair work system with the highest CVL% is worth 55.24 beats / minute. The overrated of workload can cause work stress with the results obtained 0.9000> 0.549 the employees have stress when the workload is excessively.